Employment of flexible materials in industrial products and their relationship to variables formal systems (Journal of the College of Basic Education, 2022)
Flexibility is one of the qualities that a person seeks to search for in many areas of life, given that it contributes to facilitating the tasks that he performs in any aspect of life, especially in terms of the design of industrial products. Formalism.The importance of the research lies in addressing the concept of flexible materials, their types, characteristics and applications in the field of industrial design, and knowing the underlying relationship between these materials and the formal systems of the industrial product, in addition to knowing the extents of benefit from these materials included in the industrial products that change in their formal system.